The adequacy of the number of faculty members for the actual needs of Undergraduate level students - Tishreen University - دلالة هيفاء; شكيب بشماني (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The current research aims to know the adequacy of the number of faculty members in the faculties of Tishreen University, compared to the number of undergraduate students, whether it is high or low; in light of the increase in the number of students enrolled in the university at high rates, the low numbers of faculty members in some faculties, and the growing loss of the faculty membersThe study was applied to the faculties of Tishreen University, who numbered /70.622/ male and female of undergraduate students (general education –parallel), out of /72386/ male and female students; Where the data was collected without the preparatory year students. and /1051/ faculty member in colleges; Out of /1096/ faculty member in colleges and higher institutes.Through use the learning and teaching criterion (faculty adequacy index) or (student: teacher), we concluded that there is a severe shortage of faculty members in some faculties of Tishreen University, and their inadequacy for the actual needs of students registered in the first university level.In light of the results: the researcher recommends setting the necessary plans for the numerical restructuring of the faculty members and setting a seriesof procedures, which can form the basis for developing the education policy.